2022
DOI: 10.1073/pnas.2115032119
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic gene expression and growth underlie cell-to-cell heterogeneity in Escherichia coli stress response

Abstract: Significance Individual bacteria that share identical genomes and growth environments can display substantial cell-to-cell differences in expression of stress-response genes and single-cell growth rates. This phenotypic heterogeneity can impact the survival of single cells facing sudden stress. However, the windows of time that cells spend in vulnerable or tolerant states are often unknown. We quantify the temporal expression of a suite of stress-response reporters, while simultaneously monitoring gr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
58
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(61 citation statements)
references
References 68 publications
3
58
0
Order By: Relevance
“…Studies on the oxidative stress response in bacteria have revealed characteristics that partially support each of these contrasting models (Cochran et al, 2000;de Martino et al, 2016;Hong et al, 2020;Patange et al, 2018;Sampaio et al, 2022). To resolve this uncertainty, we characterized the spatio-temporal behaviour of single E. coli cells growing in defined structured populations under a constant treatment of H2O2.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Studies on the oxidative stress response in bacteria have revealed characteristics that partially support each of these contrasting models (Cochran et al, 2000;de Martino et al, 2016;Hong et al, 2020;Patange et al, 2018;Sampaio et al, 2022). To resolve this uncertainty, we characterized the spatio-temporal behaviour of single E. coli cells growing in defined structured populations under a constant treatment of H2O2.…”
Section: Discussionmentioning
confidence: 99%
“…This indicates that while cells can reliably sense the onset of H2O2 stress and respond rapidly, the response magnitude depends on an unidentified factor that varies substantially between cells. This heterogeneity could be caused by a variety of mechanisms, including molecular stochasticity in the specific regulatory circuits or general gene expression machinery (Golding et al, 2005;Uphoff et al, 2016), cell-to-cell variation in growth or morphology (Łapińska et al, 2022;Ojkic et al, 2022;Sampaio et al, 2022) , variable cellto-cell interactions (Dal Co et al, 2020;Snoussi et al, 2018;van Gestel et al, 2021), or differences in the local environment of cells (Snoussi et al, 2018;van Vliet et al, 2018). To pinpoint the mechanisms, we designed a machine learning model using random forest regression [Figure 2A].…”
Section: Machine Learning Model Predicts Single-cell Responses To H2o2mentioning
confidence: 99%
See 2 more Smart Citations
“…After assigning reads to barcode combinations, we filtered out droplets barcodes in which a given droplet barcode had more than 8 associated plate barcodes, which corresponds to a barcode collision rate greater than 25%. We then split barcode combinations by condition (plate barcodes), and then performed another filtering step using the knee method for each condition 16 . We note that this step is important because bacteria in different conditions have different amounts of mean mRNA expression.…”
Section: Methodsmentioning
confidence: 99%